2006
DOI: 10.1111/j.1365-2524.2006.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Battle on the home care front: perceptions of home care workers of factors influencing staff retention in Northern Ireland

Abstract: The provision of home care services is a key component in avoiding inappropriate admission of older people to institutional care and preventing delayed discharge from hospital. However, there is a growing problem of retention of home care workers (HCWs), creating problems for delivering this increasingly essential service. The present study was based in a health and social services trust in Northern Ireland, and was designed to explore the growing problem of retention of HCWs from their own perspective. The cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 20 publications
10
61
0
Order By: Relevance
“…As paid, yet unqualified carers, concerns have been raised that HCAs operate in a confusing and blurred state, where they may be undervalued by qualified nursing staff, while being expected by informal carers to perform tasks which they are not qualified to do (Devlin & McIllfatrick 2010), leading to the possibility of stress (Fleming & Taylor 2007). While recognising problems arising from M a n u s c r i p t 11 the variation in HCAs' roles in the UK, (Bach et al 2008), our study shows that HCAs are able to work with the ambiguity of their role by 'getting on with whatever needs doing', thus enabling them to develop relationships with family carers and act as liaisons between family carers and health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…As paid, yet unqualified carers, concerns have been raised that HCAs operate in a confusing and blurred state, where they may be undervalued by qualified nursing staff, while being expected by informal carers to perform tasks which they are not qualified to do (Devlin & McIllfatrick 2010), leading to the possibility of stress (Fleming & Taylor 2007). While recognising problems arising from M a n u s c r i p t 11 the variation in HCAs' roles in the UK, (Bach et al 2008), our study shows that HCAs are able to work with the ambiguity of their role by 'getting on with whatever needs doing', thus enabling them to develop relationships with family carers and act as liaisons between family carers and health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…A study (Fleming & Taylor, 2007) conducted in Northern Ireland found that 44% intended to leave home care work; the main reasons for their intentions to leave were irregular working hours, lack of organizational support, and workload pressures due to being required to provide care for people with complex health and social care needs. High workload, sense of pressure, and quality of relationships with the care recipients were found to be crucial factors connected with job dissatisfaction (Kiefer et al, 2005;Piercy, 2000).…”
Section: Job Satisfaction and Turnovermentioning
confidence: 99%
“…Additionally this can also function as a significant predictor of quality of service performance (Spector, 1985). Many Taiwanese studies have investigated staff job satisfaction among individuals working in hospitals, nursing homes and schools as nurses, educators, social workers and home care workers; significant factors associated with job satisfaction include individual characteristics and the work-related context (Hwu et al, 2003;Chung and Huang, 2005;Lin and Tseng, 2005;Chen et al, 2007;Lin, 2007;Xin, 2007;Yu et al, 2008;Chou et al, 2010) Consistent findings in Western literature suggest several factors or key dimensions related to job satisfaction among home care workers (Donovan, 1989;Donovan et al, 1993;Crown et al, 1995;Denton et al, 2002;Moyle et al, 2003;Fleming and Taylor, 2006;Ejaz et al, 2008;Sherman et al, 2008). Such factors fall into two main categories: the individual characteristics of the workers and job-related factors regarding work conditions.…”
Section: Introductionmentioning
confidence: 99%